التوافق الاستراتيجي بين ادارة العمليات والاستراتيجية الشمولية للمنظمة: المفهوم والخصائص - طارق شريف يونس; عادل ذاكر النعمة (PROSPECTIVE RESEARCHES, 2023)
The Paper is an attempt to investigate major issues concerning the alignment among two critical activities, which together pave a strategic orientation for any organization The issue that discussed in depth in this paper is not a simple one. It is a problematic one, the major problem has gone to the difficulties concerning the mismatch between the organizational strategic purpose toward "Porters Generic Strategies" and the operational management purpose toward operational performance. As such that symptoms of such mismatch may be delivered to the overall mismatch among biases in strategic decisions that make wrong choice in selecting proper competitive positions for an industrial organization. Finally, the conclusion has put the ideas in terms of' solving the theoretical problem and that some criteria to support the research model